HOSPITAL ACCREDITATION: TEACHING THE HEALTH SYSTEM TO OFFER BETTER SERVICES - Machado Júnior, Celso (2024)
This article discusses the importance of studies on hospital accreditation processes and their impact on patient safety, focusing on evaluations of two health accreditation models used in Brazil: The Joint Commission International (JCI) and the National Accreditation Organization (ONA). The study, of a qualitative nature, using the document analysis method, supported by content analysis, compares the two accreditations’ models, highlighting their similarities, differences, and effectiveness in improving healthcare. Furthermore, it discusses how the implementation of these models can influence organizational culture and hospital management, factors that make it possible to guarantee the safety and quality of health services in Brazil.